On microinstabilities and turbulence in steep-gradient regions of fusion devices. (1st February 2019) - Pueschel, M J; Hatch, D R; Ernst, D R; Guttenfelder, W; Terry, P W; Citrin, J; Connor, J W
Abstract: Higher excitation states along the background field of plasma instabilities dominate over standard, ground-state eigenmodes once the gradient drive becomes sufficiently strong. At this point, mode parity can no longer be used as the sole identifier of microtearing activity. Not only ion- and electron-temperature-gradient-driven modes occur in higher states, but even trapped electron modes, where decorrelation mechanisms enable odd-parity mode structures without a vanishing bounce average. Nonlinearly, higher-order Hermite states imprint their structures on the turbulence. Even at considerably strong drive, however, quasilinear models can recover nonlinear fluxes, as long as all subdominantly unstable eigenmodes are included. Due to flux contributions from such modes, gradient scalings of fluxes can be stronger than linear expectations.